APOM and High-Density Lipoprotein are associated with Lung Function and Percent Emphysema - Burkart, Kristin M (2013)
Chronic obstructive pulmonary disease (COPD) is linked to cardiovascular disease; however, there are few studies on the associations of cardiovascular genes with COPD. We assessed the association of lung function with 2,100 genes selected for cardiovascular diseases among 20,077 European-Americans and 6,900 African-Americans. We performed replication of significant loci in the other racial group and an independent consortium of Europeans, tested the associations of significant loci with percent emphysema, and examined gene expression in an independent sample. We then tested the association of a related lipid biomarker with FEV(1)/FVC and percent emphysema. We identified one new polymorphism for FEV(1)/FVC (rs805301) in European-Americans (p=1.3×10(−6)) and a second (rs707974) in the combined European-American and African-American analysis (p=1.38×10(−7)). Both SNPs flank the gene for apolipoprotein M (apoM), a component of HDL. Both replicated in an independent cohort. SNPs in a second gene related to apoM and HDL, PCSK9, were associated with FEV(1)/FVC among African-Americans. rs707974 was associated with percent emphysema among European-Americans and African-Americans, and APOM expression was related to FEV(1)/FVC and percent emphysema. Higher HDL levels were associated with lower FEV(1)/FVC and greater percent emphysema. These findings suggest a novel role for the APOM/HDL pathway in the pathogenesis of COPD and emphysema.